The Association Between Social Adjustment and Work-Family Conflict and Organizational Citizenship Behavior in Clinical Staff of the Khatam-al-Anbia Hospital in Salmas in 2019 - Khadijeh Mokhtari; Monireh Rezaee; Esfandyar Baljani (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Clinical staff are particularly prone to work-family conflict due to their professional nature and require interdisciplinary collaboration and social adjustment to increase their job motivation and achieving success in teamwork. Objectives: The current study aimed to investigate the association between social adjustment and work-family conflict as well as organizational citizenship behavior (OCB) in hospital clinical staff. Methods: This descriptive correlational study was conducted on all (n=115) nurses and midwives working in Khatam-al-Anbia Hospital in Salmas in 2019. Data were collected using 4 questionnaires of (1) demographic information, (2) social adjustment, (3) work-family conflict, and (4) organizational citizenship behavior. Data were analyzed using SPSS version 16 by Pearson correlation, independent t-test, and one-way ANOVA. Results:: Most of the employees were female (84.5%), married (67.3%), had a bachelorchr('39')s degree (90%) and had work experience of 8.77±7.18 years. There was a significant indirect association between social adjustment and work-family conflict (r=-0>.21, p=0.05). There was no significant association between social adjustment and OCB (r=-0.06, p=0.65).Conclusion: This study demonstrated an indirect association between social adjustment and work-family conflict in hospital clinical staff. Therefore, nursing managers can improve the quality of patient care by developing employeeschr('39') adaptation skills programs intended to reduce their work-family conflict